The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4102/sajim.v21i1.946
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management processes at St Paul’s University Library in Kenya

Abstract: Background: Given the changes in society resulting from the explosion of information and knowledge in a knowledge economy, academic libraries are becoming an integral part of the knowledge system, and knowledge management is recognised as a vital process in academic libraries. The success of academic libraries in the competitive and challenging knowledge environment depends on their ability to utilise information and knowledge to meet the needs of the academic community.Objectives: This article investigates kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…The knowledge value stays low if knowledge is retained in the minds of working individuals or organisational memory until it is shared and used. Neglecting KS process and not storing and sharing metadata may lead to reduction and loss of knowledge (Shujahat et al, 2019;Singh and Singh, 2019;Sirorei and Fombad, 2019;Zaim, 2016).…”
Section: Theoretical Background and Hypothesis Formulation 21 Knowledge Management Processesmentioning
confidence: 99%
“…The knowledge value stays low if knowledge is retained in the minds of working individuals or organisational memory until it is shared and used. Neglecting KS process and not storing and sharing metadata may lead to reduction and loss of knowledge (Shujahat et al, 2019;Singh and Singh, 2019;Sirorei and Fombad, 2019;Zaim, 2016).…”
Section: Theoretical Background and Hypothesis Formulation 21 Knowledge Management Processesmentioning
confidence: 99%
“…The need for strategic management planning was suggested as a path toward improved performance in knowledge-intensive organizations; libraries are knowledge-intensive. Another case study j JOURNAL OF KNOWLEDGE MANAGEMENT j reviewed the potential for KM processes in an academic library and found that KM was utilized, but processes were not formalized through library policy or leadership buy-in (Sirorei and Fombad, 2019).…”
Section: Models Of Collaboration and Planningmentioning
confidence: 99%
“…The knowledge creation process is defined by scientists as the process of knowledge transformation through different levels of learning (García-Fernández, 2015;Känsäkoski, 2017;Claver-cortes et al, 2018), the development of existing or new competence within the organization (Probst et al, 2000;Ceptureanu & Popescu, 2018;Mahdi et al, 2019), the dynamic interaction of tacit and explicit knowledge and the transformation of individual knowledge into organizational context (Nonaka & Toyama, 2004;Sun, 2010;Rusly et al, 2012;Wee & Chua, 2013;Wahba, 2015;Little & Deokar, 2016), the ability of an organization to generate new and useful ideas and solutions (Sangari, Hosnavi, & Zahedi, 2015;Henttonen et al, 2016;Kianto et al, 2016) in order to improve processes, identify new opportunities, develop innovation (Wee & Chua, 2013;Ranjbarfard et al, 2014;Little & Deokar, 2016), increase knowledge created value (Rusly et al, 2012;Claver-cortes et al, 2018), and preserve or gain a competitive advantage (Mehralian, Nazari, Akhavan, & Rasekh, 2014;Little & Deokar, 2016;Sirorei & Fombad, 2019). Knowledge creation is defined as the development of existing and new organizational competence (knowledge, abilities and skills) in order to implement knowledge strategy, achieve organizational performance outcomes, create mutual value, and increase uniqueness and leadership in the market.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…The knowledge storage process is seen as turning an individuals' and experts' knowledge into a resource for the organization (Kotnour & Proctor, 1996;Sumbal, Tsui, See-to, & Barendrecht, 2017;Ceptureanu & Popescu, 2018;Mahdi et al, 2019), by capturing and "wrapping" knowledge (Edvardsson & Durst, 2013), by selecting, accumulating and updating knowledge (Probst et al, 2000;Acharya & Mishra, 2017;Dzenopoljac et al, 2018;Sirorei & Fombad, 2019), and by using information technology tools (Sumbal et al, 2017), in order to protect knowledge value from loss (Probst et al, 2000;Edvardsson & Durst, 2013;Kianto et al, 2016) and to access knowledge for decision making (Sangari et al, 2015). In defining the process of knowledge storage, researchers note the importance of organizational memory (Easterby-Smith & Lyles, 2011;Sangari et al, 2015;Kianto et al, 2016).…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%